Rural grievances, landholding inequality, and civil conflict - Thomson, H (Oxford University Press, 2016)
Economic grievances, particularly those caused by landholding inequality, play a central role in theories of political instability and civil conflict. However, cross-national empirical studies have failed to confirm the link between unequal distributions of land and civil war. This is due to problems in measuring and theorizing rural inequality. A measure of landholding inequality which accounts for landlessness captures economic grievances in the countryside and is predicted to be correlated with conflict. Gini coefficients of the concentration of land ownership do not only capture grievances among landowners, but also their ability to act collectively as rebels and a repressive rural elite. The relationship between landholding Ginis and conflict is shaped like an inverted 'U': inequality is associated with an increasing likelihood of conflict, but as concentration of landholdings and grievances reach very high levels the likelihood of conflict decreases with the formation of a small repressive class of landowners. Results of regressions using new data on overall land inequality and the concentration of landholdings confirm these predictions, suggesting that landholding inequality should not be ruled out as an important underlying cause of civil war.